Early career experts essential for planetary sustainability - LIM, Michelle Mei Ling (Institutional Knowledge at Singapore Management University, 2017)
Early-career experts can play a fundamental role in achieving planetary sustainability by bridging generational divides and developing novel solutions to complex problems. We argue that intergenerational partnerships and interdisciplinary collaboration among early-career experts will enable emerging sustainability leaders to contribute fully to a sustainable future. We review 16 international, interdisciplinary, and sustainability-focused early-career capacity building programs. We conclude that such programs are vital to developing sustainability leaders of the future and that decision-making for sustainability is likely to be best served by strong institutional cultures that promote intergenerational learning and involvement.